Tratamento cirúrgico de condroma extradural lombar em cão - relato de caso - Marinho, Paulo Vinícius Tertuliano [UNESP]; Jark, Paulo César [UNESP]; Avante, Michelle Lopes [UNESP]; Canola, Julio Carlos [UNESP]; De Nardi, Andrigo Barboza [UNESP]; Minto, Bruno Watanabe [UNESP] (Universidade Estadual de Londrina, 2013)
Neoplasms originating in the spinal canal are uncommon in small animal veterinary clinic, but when present can cause significant neurological signs. Anatomically, these neoplasms can be classified as extradural, intradural-extramedullary and medullary. Extradural neoplasms are located outside the dura mater, but they can cause compression of the spinal cord. The chondromas are benign neoplasms characterized by the formation of cartilage and is rarely located in the spinal canal in both human and veterinary medicine. We describe a case of lumbar extradural chondroma in a dog that surgical decompression and removal of the mass allowed the resolution of clinical signs of paralysis with return of function of the hind limbs of the patient.
Surgical treatment of lumbar extradural chondroma in a dog - Case report
Keywords: Chondroma; Extradural neoplasms; Hemilaminectomy